Jerusalem's traitor : Josephus, Masada, and the fall of Judea - Seward, Desmond, 1935-2022. (Cambridge, Mass. : Da Capo Press, 2009)
"When the Jews revolted against Rome in 66 CE, Josephus, a Jerusalem aristocrat, was made a general in his nations army. Captured by the Romans, he saved his skin by finding favor with the emperor Vespasian. He then served as an adviser to the Roman legions, running a network of spies inside Jerusalem, in the belief that the Jews only hope of survival lay in surrender to Rome. As a Jewish eyewitness who was given access to Vespasians campaign notebooks, Josephus is our only source of information for the war of extermination that ended in the destruction of Jerusalem and its Temple, and the amazing times in which he lived. He is of vital importance for anyone interested in the Middle East, Jewish history, and the early history of Christianity."--Jacket.
Introduction: The Land Where Josephus Was Born 1 -- 1 A Young Nobleman 9 -- 2 An Occupied Country 19 -- 3 Rome and Poppaea 29 -- 4 The Jew Baiter 41 -- 5 War 48 -- 6 Governor of Galilee 58 -- 7 The Return of the Legions 77 -- 8 The Siege of Jotapata 83 -- 9 The Cave and the Prophecy 93 -- 10 Josephus the Prisoner 102 -- 11 John of Gischala Comes to Jerusalem 114 -- 12 The Zealot Revolution 123 -- 13 The Reconquest of Judea 130 -- 14 Simon bar Giora 137 -- 15 The Year of the Four Emperors 145 -- 16 Titus Takes Command 155 -- 17 The Siege Begins 168 -- 18 Inside Jerusalem 185 -- 19 The Wooden Wall 194 -- 20 The Destruction of the Temple 208 -- 21 A Holocaust 223 -- 22 The Propagandist 241 -- 23 Masada and the Last Zealots 247 -- 24 A Roman Citizen 260 -- 25 History's Verdict 272.
Includes bibliographical references (pages 277-300) and index.
Keywords: Josephus, Flavius; Jews -- History -- 168 B.C.-135 A.D.; Jews -- History -- Rebellion, 66-73.; Rome -- History, Military -- 30 B.C.-476 A.D.; Palestine -- History, Military